Efektifitas Sistem Operasional Manajemen Persediaan Terhadap Kualitas Bahan Baku Di Coffe Shop Akara Coffe & Space Coffe & Space Cabang Sawangan - Djoko Hananto; Nabil Kurnia Akbar; Brian Marin Wijaya; Muhammad Alpi Saputra (PT. ALHAFI BERKAH INDONESIA, 2024)
The aim of inventory management is to ensure optimal availability of finished goods, semi-finished goods, components and raw materials, both in terms of quantity and time. The aim of this research is to study how Akara Coffe & Space manages its raw materials in order to guarantee product quality. This research method is a qualitative method with a case study approach. The research results show that Akara Coffe & Space Coffee has changed its name from Mata Kopi Purnama (MKP) due to increasingly fierce competition. They introduced the “compound” concept to allow various brands and MSMEs to interact and grow. Their favorite menu items are Osaka and gomak noodles, which provide differentiation and appeal to customers. For inventory management, they use a ROP system and record stock manually. The quality of raw materials is very important, and they use a mixture of 50% Robusta and 50% Arabica with minimum criteria of Grade A. To maintain consistent taste and quality, they use the right methods, including choosing suppliers who can provide consistent and stable coffee.